Human and Technology in the Animation Industry - Ferric Limano (Bina Nusantara University, 2021)
Humanism is a term in intellectual history that is often used in the fields of philosophy, education and literature. In classical greek times, this humanism manifested itself in paideia, a classical greek education system that was intended to translate the vision of the ideal human being. However, this classical Greek perspective departs from a purely natural view of humans. So, humans and education are like two sides of a coin that cannot be divorced. Technology is also the result of educated human beings, technology holds many beautiful promises, but in the experience and history of technology also contains threats and dangers contained in it. In this study, how to discuss the history and development of the Indonesian animation industry, from a human and technological perspective. The result of this research is to provide a viewpoint of thinking in the animation industry that humans and technology can coordinate together, resulting in many animation actors who maximize potential in animation technology.